Analisis Alih Kode Dalam Interaksi Penjual Dan Pembeli Di Pasar Mmtc Kota Medan - Yenny Marito Panjaitan; Shally Melisa; Novani Saragih; Anita Siallagan; Dasmaria Valentina Gultom; Eka Putri Saptari Wulan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
CThe role of code switching in society is very important, in relation to the use of language variations by a person or group of people, especially in language use in bilingual or multilingual communities, for example in traditional shopping centers or markets. The market, in this case the MMTC market, can be said to have its own uniqueness in relation to the use of code switching. This research is a qualitative descriptive research, while the research strategy uses a fixed case study approach, because the problems and focus of the research have been determined in the proposal before the researcher goes into the field. During the conversation, it was discovered that there was temporary code switching from Indonesian to Javanese to Indonesian carried out by traders. The incident of temporary code switching during the conversation was marked by the Javanese expression 'nek waton mbukak, lunga tak kon nlipet' 'if you just open it, go away I tell you to fold it' which was said by the trader in the middle of the speech to insinuate the buyer, then the trader returned to using Indonesian to serve buyers. Based on the results of research and discussion about code switching in the interaction of traders and buyers in the Medan MMTC market, several conclusions can be drawn. There are two types of code switching that occur in the interaction of traders and buyers in the Medan city MMTC market, namely (1) code switching based on its nature and ( 2) code switching based on the direction of switching.